2018
DOI: 10.1002/ange.201810501
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Palladium‐Catalyzed Aerobic Arylative Carbocyclization of Enallenynes

Abstract: Herein, we communicate as elective and efficient protocol for oxidative arylating carbocyclization of enallenynes using O 2 as the oxidant. The key to success for this aerobic transformation is the application of aspecific electron transfer mediator (ETM), abifunctional catalyst consisting of am etal-macrocycle and quinone moieties.T his catalyst significantly facilitates the reoxidation of Pd 0 to Pd II under atmospheric pressure of O 2 .D iverse functionalized enallenynes react with aryl boronic acids to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…In analogy with our previous report, [15] there was a rate enhancement with the hybrid catalyst compared to the use of Co(salophen) and quinone as separate molecules as shown in Figure 2. Co(salophen)‐HQ hybrid ( Cat.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…In analogy with our previous report, [15] there was a rate enhancement with the hybrid catalyst compared to the use of Co(salophen) and quinone as separate molecules as shown in Figure 2. Co(salophen)‐HQ hybrid ( Cat.…”
Section: Methodssupporting
confidence: 81%
“…During the past decade, our research group has been involved in the development of palladium‐catalyzed oxidative carbocyclizations of allenes bearing an additional unsaturated moiety, such as an olefin, alkyne, or allene [16] . Interestingly, we found that an assisting group (AG), [17] such as an olefin, alkyne or hydroxyl group, is required to make 6‐membered rings [8e,h, 15, 18] from enallenes and allenynes and to make 7‐membered rings from bisallenes due to the initial allenic C−H cleavage by Pd II (Scheme 2 a). Afterward, cascade carbocyclization and transmetallation with a nucleophile can occur and give the cyclic product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation